Mini-plate fixation versus suture suspensory fixation in cervical laminoplasty: A meta-analysis. Issue 5 (February 2017) - Liu, Feng-Yu; Ma, Lei; Huo, Li-Shuang; Cao, Yan-Xiang; Yang, Da-Long; Wang, Hui; Yang, Si-Dong; Ding, Wen-Yuan
Abstract: Background: Both the mini-plate fixation and suture suspensory fixation techniques are extensively applied in cervical laminoplasty, but which technique is superior has not been ascertained. The purpose of this meta-analysis is to compare the results between mini-plate fixation and suture suspensory fixation in cervical laminoplasty for the patients with multilevel cervical compressive myelopathy. Methods: PubMed, Embase, the Cochrane library, CNKI, and WANFANG were searched for studies that compared mini-plate fixation and suture suspensory fixation in cervical laminoplasty up to November 1, 2016. We calculated odds ratio (OR) with 95% confidence interval (CI) for dichotomous outcomes and mean difference (MD) with 95% CI for continuous outcomes. Review Manager 5.3 was used for the statistical analyses. Results: A total of 25 studies, involving 1603 participants, were included in this review. The results of this meta-analysis indicated that there were statistically significant differences in postoperative Japanese Orthopedic Association (JOA) scores (MD = 0.67, 95% CI: 0.34–0.99, P  < 0.001), JOA scores improvement rate (MD = 4.00, 95% CI: 2.51–5.50, P  < 0.001), postoperative Visual Analogue Score (VAS) (MD = −0.81, 95% CI: −1.36 to −0.26, P  = 0.004), postoperative range of motion (ROM) (MD = 4.15, 95% CI: 2.06–6.23, P  < 0.001), postoperative cervical lordosis (MD = 3.1, 95% CI: 2.02–4.18, P  < 0.001), postoperative anteroposterior diameter of the spinal canal (MD = 1.53, 95% CI: 0.11–2.95, P  = 0.03), postoperative open angle (MD = 1.93, 95% CI: 0.14–3.71, P  = 0.03), postoperative cross-sectional area of the spinal canal (MD = 37.10, 95% CI: 26.92–47.29, P  < 0.001), axial symptoms (OR = 0.28, 95% CI: 0.20–0.37, P  < 0.001), operation time (MD = 4.46, 95% CI: 0.74–8.19, P  = 0.02), and blood loss (MD = 9.24, 95% CI: 6.86–11.62, P  < 0.001). However, there was no statistically significant difference in C5 palsy (OR = 0.82, 95% CI: 0.37–1.84, P  = 0.63). Conclusions: As compared with suture suspensory fixation, mini-plate fixation in cervical laminoplasty appears to achieve better clinical and radiographic outcomes with fewer surgical complications. However, mini-plate fixation is associated with bigger surgical trauma. This conclusion should be interpreted cautiously and more high-quality, randomized controlled trials are needed in the future.